Implementation Practices of Right to Information Act 2007: Exploring Awareness, Effectiveness and Challenges (Patan Prospective Journal, 2023)
Right to Information (RTI) is a basic human right of every human being. Information makes men wise and it is competent enough to cope up with the modern world. So, it is the duty of government to inform citizens about day to day happening whatever within the government. The transformation from governance to good governance is possible, if there is possibility of increasing participation of people in governance and free access of information. By realizing this fact, Parliament of Nepal has passed Right to information act, 2007 to make government, accountable, responsible, efficient and transparent. The Purpose of this Study is to analyze the RTI implementation practices, effectiveness, assess the challenges for exercising RTI in Nepal and to evaluate the public response on RTI. For this, the researcher has applied both quantitative and qualitative methods. In addition, Survey, Questionnaire and Interview in each administrative unit of all Municipalities of Kathmandu has been used as data collection techniques. This research article can be concluded that among the entire respondents were more aware about the RTI and its provisions. It shows that media persons have better knowledge than others groups of the society. After the media, common people were also aware on RTI issues. It proves that Nepalese bureaucrats possess least knowledge among the surveyed groups on RTI issues and provisions.